Digital processing of optical emission spectra of magnetron sputtering plasma system - Afanasіeva, I.A.; Afanasiev, S.N.; Azarenkov, N.A.; Bobkov, V.V.; Gritsyna, V.V.; Logachev, Yu.E.; Okseniuk, I.I.; Skrypnyk, A.A.; Shevchenko, D.I.; Chornous, V.M. (Вопросы атомной науки и техники, 2019)
To solve the actual problem of the analysis of the sputtered particles radiation during coating deposition in a magnetron sputtering system, a digital technique was proposed for processing the emission spectra of the discharge plasma. A graphic OSA application has been created, which allows obtaining qualitative and quantitative characteristics of the magnetron discharge plasma. The obtained information about the distribution of excited particles along the direction parallel to the axis of the magnetron discharge permits one to control the mode of the discharge operation and, as a consequence, the properties of the deposited coatings. Для вирішення актуального завдання, пов'язаного з аналізом світіння розпилених частинок при нанесенні покриттів у магнетронно-розпилювальній системі, була запропонована цифрова методика обробки спектрів випромінювання плазми розряду. Створено графічний додаток OSA, що дозволяє отримати якісні та кількісні характеристики плазми магнетронного розряду. Отримана інформація про розподіл збуджених частинок вздовж напрямку, паралельного осі магнетронного розряду, дозволяє контролювати режим роботи розряду і, як наслідок, властивості нанесених покриттів. Для решения актуальной задачи, связанной c анализом свечения распыляемых частиц при нанесении покрытий в магнетронно-распылительной системе, была предложена цифровая методика обработки спектров излучения плазмы разряда. Создано графическое приложение OSA, позволяющее получить качественные и количественные характеристики плазмы магнетронного разряда. Полученная информация о распределении возбужденных частиц вдоль направления, параллельного оси магнетронного разряда, позволяет контролировать режим работы разряда и, как следствие, свойства наносимых покрытий.